Invisible Loyalties and Transgenerational Debt: Feminist Genealogy in "El cuerpo en que nací" by Guadalupe Nettel - García Rivera, René Camilo (2025)
This article examines the novel El cuerpo en que nací (Guadalupe Nettel, 2011) through the lens of feminist genealogies and transgenerational psychology. The study identifies the features of transgenerational relationships among the female characters, the transgression of invisible loyalties, and the emergence of intrafamilial debt. The analysis draws on the theoretical contributions of Alejandra Restrepo and Luce Irigaray (regarding female genealogies), as well as those of Iván Boszormenyi-Nagy and Geraldine M. Spark (in relation to transgenerational psychology). The article argues that the core of the conflict lies in the divergent loyalties within the family: while the grandmother upholds the patriarchal genealogy, the mother attempts to establish her own feminist genealogy.